Complement 5a Receptor Polymorphisms Are Associated With Panton-Valentine Leukocidin–positive Staphylococcus aureus Colonization in African Pygmies. (6th September 2018) - Schaumburg, Frieder; Witten, Anika; Flamen, Arnaud; Stoll, Monika; Alabi, Abraham S; Kremsner, Peter G; Löffler, Bettina; Zipfel, Peter F; Velavan, Thirumalaisamy P; Peters, Georg
Abstract: Panton-Valentine leukocidin (PVL) is common in African Staphylococcus aureus and can be associated with skin and soft tissue infection. PVL-positive S. aureus colonization is associated with a variant of complement receptor 5a, the cellular target of the lukS PVL subunit.